Tax evasion and the impact of international regulation: A summary of empirical results - Jakob Miethe; Helge Niesytka (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
While combating tax evasion ranks highly on the international policy agenda and journalists are covering leak after leak, the economics profession at large has somewhat neglected the subject until recently. In the last years, however, a combination of better international financial data and ingenious identification strategies in several pioneering studies has made the subject popular in empirical economics. These contributions are summarized below.
Keywords: 330